2023
DOI: 10.3390/pharmaceutics15071963
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Strategies to Improve Druggability of Potential Drug Candidates in Nonalcoholic Fatty Liver Disease Therapy

Abstract: Nonalcoholic fatty liver disease (NAFLD) has become globally prevalent and is the leading cause of chronic liver disease. Although NAFLD is reversible without medical intervention in the early stage, the condition could be sequentially worsened to nonalcoholic steatohepatitis (NASH) and, eventually, cirrhosis and hepatic cancer. The progression of NAFLD is related to various factors such as genetics, pre-disposed metabolic disorders, and immunologic factors. Thankfully, to date, there have been accumulating re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 177 publications
0
4
0
Order By: Relevance
“…This study was conducted in patients with MASH with fibrosis stage F2 or F3, with the primary endpoint of assessing improvement in at least one fibrosis stage without worsening of MASH after 24 weeks. Analysis of this part of the study showed that this outcome was achieved in 19% of patients in the placebo group compared to 36% of patients in the 28 mg efruxifermin group and 33% in the 50 mg efruxifermin group, leading the study investigators to the conclusion that efruxifermin improves liver fibrosis [49][50][51]. In light of these favorable findings, efruxifermin has entered the two ongoing placebo-controlled Phase 3 RCTs that began in late 2023.…”
Section: Fibroblast Growth Factor 21 (Fgf-21) Agonistsmentioning
confidence: 99%
“…This study was conducted in patients with MASH with fibrosis stage F2 or F3, with the primary endpoint of assessing improvement in at least one fibrosis stage without worsening of MASH after 24 weeks. Analysis of this part of the study showed that this outcome was achieved in 19% of patients in the placebo group compared to 36% of patients in the 28 mg efruxifermin group and 33% in the 50 mg efruxifermin group, leading the study investigators to the conclusion that efruxifermin improves liver fibrosis [49][50][51]. In light of these favorable findings, efruxifermin has entered the two ongoing placebo-controlled Phase 3 RCTs that began in late 2023.…”
Section: Fibroblast Growth Factor 21 (Fgf-21) Agonistsmentioning
confidence: 99%
“…Efruxifermin, which exerts an agonistic effect on FGF-21, is another promising drug from this group. This drug is a fusion protein with increased stability in the body, which consists of a human IgG1-Fc domain and two altered FGF-21 [49]. The first results of the placebo-controlled phase 2b RCT (NCT04767529) named HARMONY were published in December 2023.…”
Section: Fibroblast Growth Factor 21 (Fgf-21) Agonistsmentioning
confidence: 99%
“…This study was conducted in patients with MASH with fibrosis stage F2 or F3, with the primary endpoint of assessing improvement in at least one fibrosis stage without worsening of MASH after 24 weeks. Analysis of this part of the study showed that this outcome was achieved in 19% of patients in the placebo group compared to 36% of patients in the 28 mg efruxifermin group and 33% in the 50 mg efruxifermin group, leading the study investigators to the conclusion that efruxifermin improves liver fibrosis [49][50][51]. In light of these favorable findings, efruxifermin has entered the two ongoing placebo-controlled phase 3 RCTs that began in late 2023.…”
Section: Fibroblast Growth Factor 21 (Fgf-21) Agonistsmentioning
confidence: 99%
“…Rapid increase in the global prevalence of MASLD necessitates the development of novel treatments. The lack of available drugs for MASLD may be due to several factors, including the requirement for multifunctional agents and insufficient knowledge on key factors and appropriate drug targets for MASLD 7 . Slow and long‐term progression of the disease also poses a significant challenge to the conduct of clinical trials.…”
mentioning
confidence: 99%